Regulation of glycerol transport genes GUP1 and GUP2 in Saccharomyces cerevisiae - Oliveira, Rui Pedro Soares de (2000)
Comunicação apresentada no " 18th Small Meeting on Yeast Transport and Energetics" realizado em Ouro Preto, Brasil em 2000.